The Cambridge companion to Christian doctrine - Gunton, Colin E. (The Cambridge Companions to Religion, 1997)
What is Christian doctrine? The fourteen specially commissioned essays in this book serve to give an answer to many aspects of that question. Written by leading theologians from America and Britain, the essays place doctrine in its setting - what it has been historically, and how it relates to other forms of culture - and outline central features of its content. They attempt to answer questions such as 'what has, and does, Christian doctrine teach about God, the creation, the human condition and human behaviour?' and 'what is the part played in Christian doctrine by the Trinity, Jesus Christ and the Holy Spirit?' New readers will find this an accessible and stimulating introduction to the main themes of Christian doctrine, while advanced students will find a useful summary of recent developments which demonstrates the variety, coherence and intellectual vitality of contemporary Christian thought.